Pengembangan Aplikasi ToDoList Berbasis Mobile: Pendekatan Spiral Model untuk Mendukung Manajemen Waktu Mahasiswa: Mobile-based ToDoList Application Development: A Spiral Model Approach to Support Student Time Management - Indra Alfit; Fauzan G; Salomo Benny Junian; Fauziah Rahmasari; Nurrahmah Agusnaya; Marwan Ramdhany Edy (Journal of Deep Learning, Computer Vision, and Digital Image Processing, 2025)
The development of modern technology has driven the use of the internet in various fields, including education. Students often still use manual methods to record their activities, which are inefficient and prone to loss. Therefore, a to-do list application is needed to help students digitally record their activities. This study aims to develop an effective and efficient mobile-based ToDoList application. The application is expected to help students plan activities, set priorities, and ensure that important tasks are not missed. The development method used is the spiral model, an iterative and incremental approach that involves the stages of planning, analysis, design, implementation, testing, and evaluation in each cycle. This study emphasizes a deep understanding of user needs and the application of good interface design principles. In addition to technical development, the research also focuses on how the application can support time management and the achievement of user goals. Application testing is conducted to ensure that features function according to user expectations. Through this research, valuable insights are expected to be gained regarding the development of an effective ToDoList application that can improve users' quality of life through better time management and more efficient task completion.